Caribbean energy ministers consolidate integration in the framework of OLADE (2000)
Presents the agreement formulated at the OLADE Meeting held in Asunción, Paraguay in October 12, 2000; the joint declaration made at the Caribbean Energy Ministers Meeting held in Port-of-Spain, Trinidad and Tobago on November 14, 2000; and the terms of agreement for the establishment of the Caribbean Hydrocarbons Cooperation Commission.
Keywords: ENERGY POLICY